2008
DOI: 10.1021/ic800494h
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Control of the “Bailar Twist” in Formally d0-d2 Molybdenum Tris(dithiolene) Complexes: A Sulfur K-edge X-ray Absorption Spectroscopy and Density Functional Theory Study

Abstract: Sulfur K-edge x-ray absorption spectroscopy (XAS) and density functional theory (DFT) calculations have been used to determine the electronic structures of a series of Mo tris(dithiolene) complexes, [Mo(mdt)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
115
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(130 citation statements)
references
References 42 publications
14
115
0
1
Order By: Relevance
“…The Mo tris-dithiolene complexes are included for reference as their electronic structures have already been defined 6. The Mo(IV) complexes (red, top panel) both have significant pre-edge intensity at ~2471.3 eV.…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The Mo tris-dithiolene complexes are included for reference as their electronic structures have already been defined 6. The Mo(IV) complexes (red, top panel) both have significant pre-edge intensity at ~2471.3 eV.…”
Section: Results and Analysismentioning
confidence: 99%
“…The Mo(IV) complexes (red, top panel) both have significant pre-edge intensity at ~2471.3 eV. The pre-edge in the Mo(IV) bis-dithiolene complex (solid) has a shoulder at higher energy (2472.2 eV) while the pre-edge in the Mo(IV) tris-dithiolene (dashed) has a small contribution at lower energy (indicated by a asterisk at 2470.2 eV) due to an oxidized impurity (~10%, see reference 6). In addition, another unresolved pre-edge feature is present in the data of both the bis-and tris-dithiolene complexes at 2473.2 and 2472.7 eV, respectively.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…8,2327 X-ray absorption spectroscopy has been used to help identify the covalency of the metal-dithiolene interaction as well as determine the oxidation states for the ligand and metal. 2831 Gas-phase ultraviolet photoelectron spectroscopy (UPS) studies have shown the leveling effect that dithiolenes have on the valence ionizations. 23,32 Previous valence photoelectron studies of the molecules in Figure 2 have shown that the metal-dithiolene interaction effectively maintains the highest occupied molecular orbital ionization in a narrow energy range, which helps to level the redox potentials between d 2 , d 1 , and d 0 states during a catalytic cycle.…”
Section: Introductionmentioning
confidence: 99%
“…This increase is much smaller than the increase observed for the tris-dithiolene Mo IV and Mo VI complexes 40 (118%), which undergo a ligand-based redox process (i.e., noninnocent behavior). Thus, for the monooxo Mo IV and bisoxo Mo VI complexes, the presence of oxo ligands leads to innocent behavior of the dithiolenes where the covalent donor bonding to the Mo simply increases upon oxidation of the metal center.…”
Section: Results and Analysismentioning
confidence: 65%